A corrosion resistant die-cast Mg-9Al-1Zn anode with superior discharge performance for Mg-air battery. (September 2020) - Xiao, Bo; Song, Guang-Ling; Zheng, Dajiang; Cao, Fuyong
Abstract: The corrosion behavior and discharge performance of a die-cast (DC) Mg-9Al-1Zn (AZ91D) alloy in 3.5 wt% NaCl solution were investigated by means of immersion and electrochemical measurements in comparison with a hot-rolled (HR) AZ91D. The results indicated that the DC AZ91D had a low corrosion rate (0.10 ± 0.01 mm y −1 ), and superior discharge performance as an anode assembled in Mg-air batteries, especially at low discharge current densities. The anodic efficiency of the DC AZ91D reached 53.47% and 57.72% at 1 and 2.5 mA cm −2, respectively, which were significantly higher than that of many other Mg-based anodes. This efficiency enhancement could mainly be attributed to the uniform microstructure of the DC AZ91D with a continuous β phase network and fine matrix grains, which could produce a more protective corrosion product film. Such a uniform microstructure together with a protective product film can suppress self-corrosion and hinder the detachment of the undermined metallic pieces or the second phase particles from the substrate. Therefore, the DC AZ91D might be developed into an appropriate low cost and highly corrosion-resistant anode with superior discharge performance for Mg-air battery. Graphical abstract: Unlabelled Image Highlights: Die-casting Mg-9Al-1Zn has a more homogeneous microstructure than hot-rolled one. The die-casting corrodes at a very low rate 0.10 ± 0.01 mm/y in 3.5 wt.% NaCl. The die-casting has efficiencies 53.5% and 57.7% at +1 mA/cm 2 and + 2.5 mA/cm 2 . The die-casting's corrosion and discharge performances are superior to most Mg alloys. Die-casting is a simple method to fabricate Mg-based anodes for Mg-air batteries.